REFLECTION OF THE RIVALRY BETWEEN THE TWO ANCIENT KURDISH NATIONS, KASSITE AND MITANNI, ON THE ART OF SEALING AND SCULPTURE IN THE SECOND MILLENNIUM BC - Jehwar, Salah; Mohammad, Imad (Humanities Journal of University of Zakho, 2025)
The Kassites and Mitanni are considered ancient Kurdish nations. In the second millennium BC, there was a phenomenon of rivalry in ancient Kurdistan, especially between the Kassite and Mitannian political powers. During this period, the conflicting interests of these powers and political institutions began to compete for their own goals. These rivalries influenced the ceramic and metallurgical civilizations. This reflection describes the rivalry by depicting some intense scenes, especially the creation of scenes on pipe seals and sculptures. The artistic works and activities of poets during this period of history were able to express the conflicts and peaceful events in the environment of ancient Kurdistan through the creation of seals and sculptures. Mythological scenes were created on seals and statues; for example, the competition between humans and animals was depicted with lions and cows, and an animal hunt was depicted with a chariot. In the same field of sculpture, a scene of the creation of animals was depicted by placing a lion statue at the entrance to the street. The creation of all these animal statues such as lions, cows, and goats symbolize the power and rivalry of these nations among the political entities in the second millennium BC.